Revitalizing The Role of Pangeran Jaya Cooperative In Strengthening The Economy of The Community of Ogan Komering Ilir District - Rakhmat, Acip; Zuliansyah, Muhammad Andri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
This community service aimed to increase the understanding of the management, members and the community about the importance of the role of Pangeran Jaya Cooperative in strengthening the economy by choosing and running a business in accordance with the wants and needs of the members and the community of Ogan Komering Ilir District. The service activities were carried out at Pangeran Jaya Cooperative, Talang Pangeran Village, Teluk Gelam Subdistrict, Ogan Komering Ilir District. The location of the study was selected purposively. The method used counseling and interactive discussions with all participants to increase their understanding on the important role of Pangeran Jaya Cooperative both as business partners and partners in meeting family needs. The study found out that during its establishment from 2015 to 2022, Pangeran Jaya Cooperative did not carry out the role and function of its cooperative business (category E/inactive), lack of knowledge and understanding of the management and members. The business run by the cooperative was not in accordance with the needs of members and the lack of accountability and transparency of the management showed that it never held an annual member meeting (RAT) resulting in the non-running of the cooperative. In an effort to revitalize the Cooperative, capacity building is needed for both cooperative institutions and human resources to increase the service capacity and develop partnership cooperation with other institutions/business entities.